Targeted Degradation of Abscisic Acid Receptors Is Mediated by the Ubiquitin Ligase Substrate Adaptor DDA1 in Arabidopsis . Issue 2 (21st February 2014) - Irigoyen, María Luisa; Iniesto, Elisa; Rodriguez, Lesia; Puga, María Isabel; Yanagawa, Yuki; Pick, Elah; Strickland, Elizabeth; Paz-Ares, Javier; Wei, Ning; De Jaeger, Geert; Rodriguez, Pedro L.; Deng, Xing Wang; et al.
Abstract : CULLIN4-RING E3 ubiquitin ligases target proteins for proteasomal degradation, thus regulating plant developmental and stress responses. The ubiquitin ligase substrate adaptor DDA1 binds to and promotes destabilization of the abscisic acid (ABA) receptor PYL8, thereby attenuating ABA-mediated responses through desensitization, and ABA counteracts the destabilization of PYL8. Abstract: CULLIN4-RING E3 ubiquitin ligases (CRL4s) regulate key developmental and stress responses in eukaryotes. Studies in both animals and plants have led to the identification of many CRL4 targets as well as specific regulatory mechanisms that modulate their function. The latter involve COP10-DET1-DDB1 (CDD)–related complexes, which have been proposed to facilitate target recognition by CRL4, although the molecular basis for this activity remains largely unknown. Here, we provide evidence that Arabidopsis thaliana DET1-, DDB1-ASSOCIATED1 (DDA1), as part of the CDD complex, provides substrate specificity for CRL4 by interacting with ubiquitination targets. Thus, we show that DDA1 binds to the abscisic acid (ABA ) receptor PYL8, as well as PYL4 and PYL9, in vivo and facilitates its proteasomal degradation. Accordingly, we found that DDA1 negatively regulates ABA -mediated developmental responses, including inhibition of seed germination, seedling establishment, and root growth. All other CDD components displayed a similar regulatory function, although they did not directly interact with PYL8. Interestingly, DDA1-mediated destabilization of PYL8 is counteracted by ABA, which protects PYL8 by limiting its polyubiquitination. Altogether, our data establish a function for DDA1 as a substrate receptor for CRL4-CDD complexes and uncover a mechanism for the desensitization of ABA signaling based on the regulation of ABA receptor stability.